Serum Catestatin Levels and Its Relationship with Disease Activity in Patients with Ankylosing Spondylitis - Alisik, Tugba; Altan, Yagmur Cagla Reis; Alisik, Murat; Nacir, Baris (Archives of Rheumatology, 2025)
Background/Aims: Catestatin (CST) is a bioactive peptide with wellestablished cardiovascular roles, including anti-inflammatory and metabolic effects. This study aimed to compare the serum CST levels in patients with ankylosing spondylitis (AS) and healthy control subjects. Materials and Methods: This cross-sectional study included 95 patients with AS who met the Assessment of SpondyloArthritis International Society classification criteria for AS and 85 healthy individuals. Demographic, clinical, and laboratory parameters were recorded. Serum CST levels were measured by commercially available enzyme-linked immunosorbent assay kits. Results: Median serum CST levels were significantly lower in patients with AS compared to the control group (2.57 [1.74-4.58] vs 9.4 [3.55-26.6] ng/mL, P < .001). Catestatin levels were lower in the active AS group than in the inactive AS and control groups (P < .05). Significant negative correlations were found between CST and age, ankylosing spondylitis disease activity score–C-reactive protein (ASDAS-CRP), and C-reactive protein. Multiple linear regression analysis demonstrated that serum CST levels were significantly associated with the ASDAS-CRP group variable after model adjustment for sex, age, body mass index, HLA-B27 status, disease duration, and medications. Conclusion: These findings suggest that CST may play a role in the complex pathophysiology of AS. However, future multicenter longitudinal studies are necessary to further elucidate the relationship between CST and AS.